Analysis of GTAW and FCAW Welding in Impact Testing in Steel Micro Structures - Muhamad Farhan; Wilarso; Aswin Domodite; Awang Surya (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2024)
Welded joints, which encompass the criteria of welding base metal connections in the material, welding speed, material quality, and material toughness, are an integral aspect of tank construction. Steel material joints frequently fail during the Gas Tungsten Arc Welding (GTAW) and Flux Cored Arc Welding (FCAW) welding procedures because air droplets become trapped in the steel material during the welding process. Finding the primary reasons for welding failures is the goal of this study. Impact and microstructure testing are used in the welding research method on SS400 steel. The FCAW welding process uses E71T-1C (Kobe) Electrodes Steel Familiarc AWS A5.2 E71T-1C) at varying currents of 80 A (Root), 100 A (Filler), and 120 A (Capping), against SS400 steel plate material with a thickness of 10 mm x 200 mm x 200 mm in V Buut seams Joints. The GTAW ER 70 SG (Familiarc Filler/Rods TG-S51T) Electrode classification allows for 90 A (Root), 110 A (Filler), and 120 A (Capping). Plate 1 has a value of 36.3 kJ/inch in the heat input calculation findings at the three section sites, while Plate 2 has the highest value of 61 kJ/inch. In the meantime, FCAW plate 2 has an impact strength value of 142.1 J, and plate 1 has an average hit in the test results at each of the three places of the specimen, according to the impact test findings. Three welding parameter points were used to record the findings of the metallographic testing's microstructure observations. plates 1 and 2 on the capping, filler, and root. being aware of the areas in the welded junction between plates 1 and 2 that are impacted by heat in the microstructure. Because of the material's strong heat input, which makes the steel brittle and promotes the formation of pearlite rather than ferrite, plate 2 has the highest value in the impact test